Implementasi Konseling Pastoral dalam Penguatan Identitas Diri Anak yang Mengalami Rendah Diri di Lingkungan Pendidikan - Bahagia Tarigan Tarigan (Program Studi Bimbingan dan Konseling FKIP UMSU, 2026)
Low self-esteem among children and adolescents in educational settings is not merely a transient emotional issue but a condition that can impede identity formation and erode self-worth over the long term. Most school-based interventions have relied on psychological-cognitive approaches, while the relational-spiritual dimension at the heart of pastoral counseling has rarely been integrated conceptually. This article aims to construct a conceptual framework explaining how pastoral counseling—through its five functions of healing, sustaining, guiding, reconciling, and nurturing—can strengthen the self-identity of children experiencing low self-esteem. The study employs an integrative conceptual review combined with a descriptive qualitative case-study design intended to guide further inquiry. A synthesis was conducted across 42 verified sources spanning identity development, self-esteem, social withdrawal, spirituality, and pastoral practice in schools. The synthesis is formulated into six propositions linking pastoral functions to children's psychological needs, with the values of love, acceptance, forgiveness, and hope as connecting mechanisms. The proposed framework positions a relational safe space and a supportive ecosystem—teachers, counselors, pastoral caregivers, families, and peers—as prerequisites for strengthening positive self-concept, self-acceptance, and courage. This article contributes an empirically testable theoretical model and offers a reference for holistic education that honors the wholeness of the child.